Efficiency of insecticides, applied as seed treatment and in plant pulverization in the control of green belly stink bug, Dichelops melacanthus (Dallas) (Hemiptera: Pentatomidae), in corn crop. - Ávila, Crébio José; Duarte, Marcela Marcelino (BioAssay, 2012)
The efficiency of the insecticide tiametoxam applied as seed treatment (210 g i.a. /100 kg), the mixture tiametoxam + lambda-cialotrina (16,5 + 33 and 33 + 66 g i.a. /ha) applied as plant pulverization and the association of both treatments in the control of Dichelops melacanthus adults on corn crop were evaluated. The experiment was carried out at greenhouse and field conditions, with five chemical treatments and one check treatment (without insecticide). The seed treatment was done one day before field sowing. Ten days after the complete plant emergence (in greenhouse and field) the pulverization was done with tiametoxam + lambda-cialotrina. Then, adults of green belly stink bug were liberated to feed on corn plants, being used screen cages for contention of the insects. The survival of adults of D. melacanthus was significantly influenced by chemical treatments applied both on seeds and in corn plant pulverization either at greenhouse or at field conditions. At greenhouse conditions, it was observed better control of adults when tiametoxam was applied on corn seeds, independently if the corn plants were sprayed or not with the mixture tiametoxam + lambda-cialotrina. However, at field conditions, the mixture tiametoxam + lambda-cialotrina sprayed on corn plant was more efficient in the control of green belly stink bug than tiametoxam applied on seeds.